E-RECORDS MANAGEMENT AND GOVERNANCE IN EAST AND SOUTHERN AFRICA - Wamukoya, Justus; M. Mutula, Stephen (Malaysian Journal of Library and Information Science, 2005)
This paper reviews the status of e-records management in East and Southern Africa. The region faces major challenges with regards to the management of records and archives due to historical, political, cultural, managerial and technological factors. This paper examines the e-records readiness in institutions with statutory responsibility for records and the implications of e-records management for governance. The paper also suggests ways to rectify the e-records management problems in the East and Southern Africa member countries